Manajemen Pengelolaan Utang pada Rumah Tangga Kelas Menengah di Kota Pontianak - Dina Amaliah Maulida; Dwi Surya Atmaja; Syahbudi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Basically, debt in Islam is seen as an instrument that can help in meeting the needs of individuals or groups in need, but also has a side that needs to be considered so as not to cause harm or injustice. Due to poor financial management, some people today are more likely to go into debt. Many people go into debt to make ends meet, and the desire to owe comes from wanting to have an amount of money that is greater than their income. It is very important to carry out financial management in married life because the consumptive tendencies of modern society cause irresponsible financial management. This research is an interdisciplinary research that is exploratory, exploratory research does not require certain hypotheses or theories. Researchers only prepare a few questions as a guide to obtain primary data in the form of information, information, as initial data needed. There are two data sources, primary data and secondary data, data analysis techniques using observation, interviews and documentation. The interview results show that debt management in middle-class households in Pontianak City is influenced by various factors, including needs, income, and awareness of the importance of managing debt wisely. In many cases, good debt management plays a key role in maintaining family economic stability